2017
DOI: 10.14254/2071-789x.2017/10-2/5
|View full text |Cite
|
Sign up to set email alerts
|

Boards’ Attributes and Company Performance: the Romanian Experience

Abstract: ABSTRACT. For a long period of time, researchers from the corporate governance field have been interested in finding out what drives companies' performance. The present study identifies five attributes of boards -size, age, female representation, proportion of non-executive directors, and chairman-CEO duality -in an attempt to link these to diversification strategy and financial performance. These relations are investigated using archival sources of data for a sample of 56 publicly traded companies from an eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…For these reasons, this study tested whether the environmentally sensitive industry status exhibits a moderating effect on waste information disclosure and financial performance. Moreover, several previous studies [ 62 , 63 , 64 , 65 , 66 , 67 ] have shown that the size and structure of the board of directors influence the financial performance of companies. So, another goal was to test whether the number of directors on the board exerts a moderating effect between waste management information disclosure and financial performance.…”
Section: Methodsmentioning
confidence: 99%
“…For these reasons, this study tested whether the environmentally sensitive industry status exhibits a moderating effect on waste information disclosure and financial performance. Moreover, several previous studies [ 62 , 63 , 64 , 65 , 66 , 67 ] have shown that the size and structure of the board of directors influence the financial performance of companies. So, another goal was to test whether the number of directors on the board exerts a moderating effect between waste management information disclosure and financial performance.…”
Section: Methodsmentioning
confidence: 99%
“…e relationship between the size of the board of directors and the financial performance of companies is explained by the theory of resource dependence [91]. us, proponents of this theory argue that a larger number of board members will lead to a greater accumulation of resources [92]. However, opinions are divided and so we find that some support the idea that larger councils are more likely to impact performance indicators favorably [93][94][95][96][97] and argue that smaller boards are more efficient and enhance the performance of companies.…”
Section: Board Size Andmentioning
confidence: 99%
“…Almost directors are from man members [1]. Most of prior study in emerging market find the number of women on board is still low such as in Indonesia [24], [25] and Malaysia [13].…”
Section: Gender Diversitymentioning
confidence: 99%
“…Researches on Board of Directors charactheristics and company performance have received much intention until now [1]. Board of Directors has a significant contribution in enhancing value of stakeholders.…”
Section: Introductionmentioning
confidence: 99%